2017
DOI: 10.7324/japs.2017.70133
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals from mulberry extract (Morus sp.): Antioxidant and neuroprotective potentials

Abstract: ROS are involved in aging, progressive neuronal death, and age related disorders. During the last decade, there is increasing evidence indicating the beneficial role plant rich phytochemicals for the treatment of oxidative stress-induced disorders in the brain due to their antioxidant activity. Mulberry extract has been reported to have antioxidant activity which attenuates deleterious effects of oxidative stress. Their neuroprotective effects in vitro and in vivo models of neurodegenerative disorders have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Mechanisms of action of polyphenols mulberry extracts and related compounds as neuroprotectors in brain damage and aging was found by Rebai et al, [27] which is also active for brain disorder that can be effective for pest control which was revealed in our experiments. As the present investigation was carried on plant based pesticides or botanicals so it follows the traditional practice of pest control.…”
Section: Discussionsupporting
confidence: 73%
“…Mechanisms of action of polyphenols mulberry extracts and related compounds as neuroprotectors in brain damage and aging was found by Rebai et al, [27] which is also active for brain disorder that can be effective for pest control which was revealed in our experiments. As the present investigation was carried on plant based pesticides or botanicals so it follows the traditional practice of pest control.…”
Section: Discussionsupporting
confidence: 73%
“…It has also been reported that mulberries contain several bioactive phytochemicals like anthocyanins, phloridzin (Figure 2), quercetin (Figure 2), chlorogenic acid (Figure 2), resveratrol (Figure 2), rutin (Figure 2) (Gundogdu et al, 2011;Shrikanta et al, 2015;Tomas et al, 2015;Yang et al, 2016). The presence of phytochemicals and nutraceuticals in mulberries is responsible for a synergistic and diversified biological activities such as anticancer (Aggarwal et al, 2004), antioxidant (Jiang et al, 2013), anti-diabetic (Wang et al, 2013;Swathi et al, 2017), neuroprotective (Rebai et al, 2017), hepatoprotective (Deniz et al, 2018), anti-inflammatory (Chen et al, 2016b), antibacterial (Budiman et al, 2017), anti-obesity (Peng et al, 2011), and hypolipidemic activities (Yang et al, 2010). Availability of required nutrients and phytochemicals from the plant sources is essential.…”
Section: Introductionmentioning
confidence: 95%
“…Neuroprotective activity of mulberry fruit extracts has been reported through in-vivo and in-vitro models of neural disorders (Rebai et al, 2017). The study was performed to know the effect of mulberry fruits extracts on Parkinson's disease.…”
Section: Neuroprotectivementioning
confidence: 99%
“…Mulberry is a multi-functional plant and a great source of nutrients and phytochemicals, which include flavonoids, which have antioxidant activity and phenolic constituents with major active components of biological activities (Rebai et al, 2017). According to Srivastava et al (2006) Mulberry has also been established as functional food due to health promotion and disease prevention.…”
Section: Mulberry Plantmentioning
confidence: 99%